Diaspora and Trust : Cuba, Mexico, and the Rise of China - Hearn, Adrian H. (2016)
Diaspora and Trust charts changing Sino-Latin relations at the outset of the 21st century. Combining political-economic analysis with ethnography, the book examines the responses of Cuba and Mexico to China’s growing global influence. Despite opposite economic policy orientations, neither Latin American country has successfully adapted to new conditions of cooperation and competition with China. Furthermore, Cuba and Mexico both struggle with uncertain relationships to the Chinese diaspora communities within their borders. TRUST AND DIASPORA draws on fieldwork in all three countries, providing a rich account of personal experiences at the intersection of global and local affairs. In the process, author Adrian H. Hearn advocates a paradigm for international relations and economic development predicated on the idea of trust. Hearn’s study theorizes trust as an alternative to existing models of exchange, including those based on social capital in the West and traditional Confucian values in China. The book argues convincingly for trust as a foundation for fruitful change in a globalized Cuba and Mexico and as a key to new balances of state, private, and civic power necessitated by the rise of China.This title was made Open Access by libraries from around the world through Knowledge Unlatched.